OP0256 ADAM17 And Galectin-9 are Critical Regulators of Local 4-1BB Activity and Disease Outcome in Rheumatoid Arthritis. (9th June 2015) - Nielsen, M.A.; Andersen, T.; Etzerodt, A.; Kragstrup, T.; Rasmussen, T.; Stengaard-Pedersen, K.; Hetland, M.; Hørslev-Petersen, K.; Østergaard, M.; Hvid, M.; Moestrup, S.; Deleuran, B.
Abstract : Background: In rheumatoid arthritis (RA) 4-1BB (TNFSFR9) is believed to be involved in the continued T cell activation within the inflamed joint. 4-1BB binds to 4-1BB ligand (4-1BBL) generating local clonal expansion and accumulation of antigen-specific effector-type T cells. Galectin-9 (Gal-9) is upregulated at site of inflammation and has recently been suggested to be a restricting factor for the inflammatory signal of 4-1BB. ADAM17 (TACE) has previously been linked to RA and inflammation. It is a sheddase with a broad substrate specificity although it is best know for its involvement in TNFα release by being the main sheddase of proTNFα. Objectives: To determine the role of the interplay between 4-1BB, ADAM17 and Gal-9 in RA. Methods: 4-1BB and Gal-9 expression was studied in paired peripheral blood mononuclear cells (PBMC) and synovial fluid mononuclear cells (SFMCs) by flow cytometry in chronic RA (cRA), and in PBMCs from healthy volunteers (HV). 4-1BBL, Gal-9, and TNFα were used to stimulate SFMCs. Surface plasmon resonance analysis was performed with human recombinant proteins 4-1BB, 4-1BBL, and Gal-9. Transfected HEK293 cells expressing 4-1BB were established to investigate potential sheddases of 4-1BB. Soluble 4-1BB was measured by ELISA in plasma from treatment naïve early RA (eRA) patients obtained at treatment initiation (the OPERA regimen, n=96) 1 . Results: In chronic RA (cRA), the percentage of T cells expressing 4-1BB was significantly higher in SFMCs compared with PBMCs and in cRA PBMCs compared with HV PBMCs (both p<0.01). After TNFα stimulation of SFMCs the percentage of 4-1BB-positive T cells doubled (p<0.05). Stimulation of RA SFMC cultures with 4-1BBL only increased the TNFα production when combined with Gal-9, confirming that Gal-9 is pivotal for the function of 4-1BB in RA (p<0.05). When HEK293 cells expressing 4-1BB were incubated with PMA, the level of s4-1BB doublet (p<0.05). The role of ADAM17 in this process, was confirmed by RNAi mediated ADAM17 knockdown, which decreased the shedding of 4-1BB to the level of control and mock-transfected cells (p<0.05). The plasma concentration of s4-1BB was significantly elevated in eRA patients at baseline compared with HV (P<0.01). Baseline s4-1BB associated with baseline SJ40 and DAS28CRP at 24 months (both p<0.05)). Furthermore, the ability to sustain high s4-1BB plasma levels correlated with progression in TSS after 12 month (ρ =0.25, p=0.02). Conclusions: ADAM17 induces 4-1BB shedding in RA and is connected to TNFα metabolism. Gal-9 is pivotal for the local function of 4-1BB in RA. Furthermore, high plasma levels of s4-1BB are associated with number of swollen joints, but also with a good prognosis measured by DAS28CRP and TSS. 4-1BB metabolism thereby plays a central role in the delicate network of pro- and anti-inflammatory factors in RA. References: Hørslev-Petersen et al. Ann rheum Dis. 2013 Disclosure of Interest: None declared